Protective effects of certain pharmacological agents in monocrotaline - induced pulmonary hypertension in rats - Alarqam Zaki Obaid Almohammedi; Azza Mounir Agha; Hala Fahmy Zaki; Lamiaa Ahmed Ahmed Atti (Cairo : Alarqam Zaki Obaid Almohammedi, 2014)
The pulmonary hypertension is a progressive disease of various origins that is characterized by the elevation of pulmonary arterial pressure and death due to right ventricular dysfunction. In the present study, the possible protective effect of L- arginine, diosgenin and naringenin were investigated in monocrotaline - induced pulmonary hypertension in rats. Pulmonary hypertension was induced by a single subcutaneous injection of monocrotaline (60 mg/kg). Oral doses of L- arginine (500 mg / kg), diosgenin (100 mg / kg) and naringenin (50 mg / kg) alone or in combination were daily administered for 3 weeks. At the end of the experiment, mean arterial blood pressure, electrocardiography and echocardiography were recorded. Rats were then sacrificed and serum was separated for determination of total nitrate / nitrite level
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacology and Toxicology
Issued also as CD
Keywords: Diosgenin; L- arginine; Monocrotaline